The production of (in)security in São Paulo: changing patterns of daily actions from the perspective of social practices theory - Haubrich, Dominik; Wehrhahn, Rainer (ERDKUNDE, 2020)
The growing research on public security policy in the context of urban crime and insecurity largely re-flects a shifting paradigm towards a new culture of control. At the same time, research has rarely asso-ciated descriptive studies about the emergence of insecurities with discourses, policies and measures that aim at the production of greater urban security. This paper seeks to address this comparison through exploring the interwovenness of security practices and arrangements in everyday life. Drawing on the theory of social practices and the interaction of agencies and structures – institutions, policies and discourses at different scales – we argue that there is a mutual interrelation between public and private security policies on the one hand and the space-related everyday practices of urban middle-class residents on the other hand. Taking two districts located in the city of São Paulo as examples, the paper presents the results of 70 qualitative interviews with inhabitants concerning the nexus of doings and sayings in everyday practices in the context of different (in-)security production processes. We discuss how these security practices emerge as the grounding concept of shifting public security and neighbourhood at the local level. Thus, the main purpose of the paper is to theoretically overcome the conceptual dualism of reading sociality in public and private (in-)security by putting social practices theory empirically into practice.